Development of Comic-Based Teaching Materials in Elementary Schools - Sri Wulan Anggraeni; Yayan Alpian; Depi Prihamdani; Tia Damayanti (Indonesian Journal of Social Research (IJSR), 2023)
This research aims to produce comic-based teaching materials for elementary schools and determine the feasibility of this comic-based teaching material. This research is a type of research and development research (R&D). This research was conducted in elementary schools using fourth-grade students as research subjects. Observation, interviews, and questionnaires were used as data-collecting methods and were all descriptively examined. The findings of this study include comic-based teaching materials, in which material experts have given a feasibility rating of 91%, 93% by language experts, and 94% by media experts. The three expert assessments are included in the "very feasible" category. The experimental class's learning outcomes differ on average from those of the control class, which is 85,47, and the control class, which is 80.63, and 100% of students complete the minimum completeness criteria. Based on the t-test analysis, The experimental class's effectiveness of student learning outcomes is superior to that of the control class where t count = 3.84 > t table (α5%) = 2.00. Conclusion: Comic-based teaching materials are ideal for the learning process and for improving learning outcomes for students who can create a fun learning atmosphere